A school microepidemic of tuberculosis. Issue 12 (December 1991) - Bredin, C P; Godfrey, M; McKiernan, J
Abstract : BACKGROUND: Microepidemics of tuberculosis continue to occur in countries with a low incidence of tuberculosis. METHODS AND RESULTS: A microepidemic of tuberculosis in a secondary school with 604 girls in Cork city, Ireland, in 1986 with follow up to 1990 is described. Neonatal BCG vaccination was discontinued in the city in December 1972 so most of the 342 pupils who had received BCG were aged 14 years or more. Six active cases and 75 tuberculin positive cases were found. Four of the six girls with active disease had had neonatal BCG. The 75 pupils with a positive (grade 3 or 4) Heaf test response were given chemoprophylaxis with rifampicin and isoniazid for six months; none had developed active tuberculosis four years later. The brother of the girl who was the probable index case, however, developed active tuberculosis in 1988 despite similar chemoprophylaxis. CONCLUSION: The episode highlights the fact that children who have had neonatal BCG can develop active tuberculosis as teenagers.